2009
DOI: 10.1051/0004-6361/200912246
|View full text |Cite
|
Sign up to set email alerts
|

The ESO/VLT 3rd year Type Ia supernova data set from the supernova legacy survey

Abstract: Aims. We present 139 spectra of 124 Type Ia supernovae (SNe Ia) that were observed at the ESO/VLT during the first three years of the Canada-France-Hawaï Telescope (CFHT) supernova legacy survey (SNLS). This homogeneous data set is used to test for redshift evolution of SN Ia spectra, and will be used in the SNLS 3rd year cosmological analyses. Methods. Spectra have been reduced and extracted with a dedicated pipeline that uses photometric information from deep CFHT legacy survey (CFHT-LS) reference images to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 41 publications
1
104
0
Order By: Relevance
“…This is known to be feasible at z < 1 (e.g. Zheng et al 2008;Balland et al 2009;Blondin et al 2012). In the next decade, we can seriously consider extending the spectroscopic comparisons of SNe across redshifts and host types to higher redshifts than currently available: both the JWST and ground-based extremely large telescopes (Hook 2013) will provide relatively easy access to mid-resolution spectroscopy of faint targets (m ∼ 26) in the NIR, not practical with current instruments.…”
Section: Spectroscopy Of "Live" Supernovae and Metallicity Diagnosticsmentioning
confidence: 99%
“…This is known to be feasible at z < 1 (e.g. Zheng et al 2008;Balland et al 2009;Blondin et al 2012). In the next decade, we can seriously consider extending the spectroscopic comparisons of SNe across redshifts and host types to higher redshifts than currently available: both the JWST and ground-based extremely large telescopes (Hook 2013) will provide relatively easy access to mid-resolution spectroscopy of faint targets (m ∼ 26) in the NIR, not practical with current instruments.…”
Section: Spectroscopy Of "Live" Supernovae and Metallicity Diagnosticsmentioning
confidence: 99%
“…It originates from the union of two sources: 241 are real-time selected events confirmed as "Ia" or "Ia?" by spectroscopy (Howell 2005;Bronder et al 2008;Ellis et al 2008;Balland et al 2009), and the additional 48 are issued from a SN Ia photometric selection by Bazin et al (in prep. ) based on the host galaxy photometric redshift.…”
Section: Snls Data and Simulation Descriptionmentioning
confidence: 99%
“…The accelerated expansion is currently widely attributed to the existence of a "dark energy" component, which is compatible with Einsteinʼs cosmological constant. Over the last decade, the sample of SNe Ia has increased dramatically (e.g., Astier et al 2006;Wood-Vasey et al 2007;Bailey et al 2008;Kowalski et al 2008;Balland et al 2009;Freedman et al 2009;Hicken et al 2009;Kessler et al 2009;Amanullah et al 2010;Contreras et al 2010;Suzuki et al 2012;Betoule et al 2014;Rest et al 2014), and it now comprises several hundred spectroscopically confirmed SNe Ia. Since SNe Ia probe the low-redshift universe, they are ideal tools to measure the properties of dark energy.…”
Section: Introductionmentioning
confidence: 99%